Financial Literacy, Financial Behavior (FoMO), and Influencers Determinants of Investment Decision Members of the Investment Gallery Forum of the Capital Market Study Group in Semarang City - Erfina Vesnia Budiyanti; Agus Prayitno; Diana Puspitasari; Maria Safitri (Faculty of Economics and Business Universitas Dian Nuswantoro, 2026)
This study aims to analyze the influence of financial literacy, financial behavior (Fear of Missing Out/FoMO), and influencers on investment decision-making among members of the Investment Gallery – Capital Market Study Group in Semarang City. The research employed a quantitative approach using purposive sampling, involving 155 respondents consisting of members, administrators, and interns of investment galleries who already possess a Single Investor Identification (SID). Data were collected through questionnaires and analyzed using multiple linear regression with the help of SPSS 25. The results reveal that all three independent variables—financial literacy, financial behavior (FoMO), and social media influencers—have a positive and significant effect on investment decisions. Among these variables, financial literacy has the most dominant influence with a coefficient value of 0.706, followed by financial behavior (FoMO) with 0.194, and influencers with 0.134. Collectively, these variables explain 48.1% of the variation in investment decision-making. The findings indicate that a strong understanding of financial concepts, psychological motivation to avoid missing out, and digital social influence from credible influencers are key factors shaping rational investment decisions among young investors.